Intermittent lipid nanoparticle mRNA administration prevents cortical dysmyelination associated with arginase deficiency - Suhail Khoja; Xiao-Bo Liu; Brian Truong; Matthew Nitzahn; Jenna Lambert; Adam Eliav; Eram Nasser; Emma Randolph; Kristine E. Burke; Rebecca White; Xuling Zhu; Paolo G.V. Martini; et al. (Molecular Therapy: Nucleic Acids, 2022)
Arginase deficiency is associated with prominent neuromotor features, including spastic diplegia, clonus, and hyperreflexia; intellectual disability and progressive neurological decline are other signs. In a constitutive murine model, we recently described leukodystrophy as a significant component of the central nervous system features of arginase deficiency. In the present studies, we sought to examine if the administration of a lipid nanoparticle carrying human ARG1 mRNA to constitutive knockout mice could prevent abnormalities in myelination associated with arginase deficiency. Imaging of the cingulum, striatum, and cervical segments of the corticospinal tract revealed a drastic reduction of myelinated axons; signs of degenerating axons were also present with thin myelin layers. Lipid nanoparticle/ARG1 mRNA administration resulted in both light and electron microscopic evidence of a dramatic recovery of myelin density compared with age-matched controls; oligodendrocytes were seen to be extending processes to wrap many axons. Abnormally thin myelin layers, when myelination was present, were resolved with intermittent mRNA administration, indicative of not only a greater density of myelinated axons but also an increase in the thickness of the myelin sheath. In conclusion, lipid nanoparticle/ARG1 mRNA administration in arginase deficiency prevents the associated leukodystrophy and restores normal oligodendrocyte function.